Rose Harbor in bloom : a novel - Macomber, Debbie (New York : Ballantine Books, 2013)
In Cedar Cove three women -- innkeeper Jo Marie Rose, young Annie Newton, and high-powered businesswoman Mary Smith -- make peace with their pasts as they boldly welcome their futures
Keywords: Hotelkeepers -- Fiction; Life change events -- Fiction; Domestic fiction